“Losing the Phobia:” Understanding How HIV Pre-exposure Prophylaxis Facilitates Bridging the Serodivide Among Men Who Have Sex With Men - Koester, Kimberly A.; Erguera, Xavier A.; Kang Dufour, Mi-Suk; Udoh, Ifeoma; Burack, Jeffrey H.; Grant, Robert M.; Myers, Janet J. (Frontiers in Public Health, 2018)
The use of HIV serostatus information has played a pivotal role in partner selection norms. A phenomenon known as serosorting is the practice of selecting a partner based on a perception that they are of the same HIV status in order to avoid transmission from one partner to the other. An understudied aspect of serosorting is that it has a divisive effect – one accepts or rejects a potential partner based on a singular characteristic, the partner’s HIV status, and thus excludes all others. This division has been formally referred to as the HIV serodivide. In this study, we explored partner selection strategies among a group of HIV-negative, young men who have sex with men (n=29) enrolled in a PrEP demonstration project in Northern California. We found that trends in serosorting were in fact shifting, and that a new and opposite phenomenon was emerging, something we labeled ‘seromixing’ and that PrEP use played a part in why norms were changing. We present three orientations in this regard: 1) maintaining the phobia: in which men justified the continued vigilance and exclusion of people living with HIV as viable sex or romantic partners, 2) loosening/relaxation of phobia: among men who were reflecting on their stance on serosorting and its implications for future sexual and/or romantic partnerships, and 3) losing the phobia: among men letting go of serosorting practices and reducing sentiments of HIV-related stigma. The majority of participants spoke of changing or changed attitudes about intentionally accepting rather than rejecting a person living with HIV as a sex partner. For those who maintained strict serosorting practices, their understandings of HIV risk were not erased as a result of PrEP use. These overarching themes help explain how PrEP use is contributing to a closing of the HIV serodivide.